(untitled) (Revista Apotheke, 2025)
The article refers to the result of a research in/about Visual Arts/Painting and in/about Art/Education, aimed at analyzing the teaching/learning methodology of two disciplines of Painting of the Teaching Degree Course in Visual Arts of the Federal University of Pará. It focused on the following question: How can artistic practices influence and be influenced by pedagogical practice? The methodology adopted was the Triangular Approach: Read, Do/Create and Contextualize. In an ethnographic turn in contemporary art, which involved (auto)biographies, the artist/teacher/researcher paradigm, it is concluded that it is impossible to separate the professional self from the personal self and the importance of investigations that reflect the intersections between artistic creation and teaching in Visual Arts/Painting in Higher Education.